Moon tides : Jeju Island grannies of the sea - Sunoo, Brenda Paik (Seoul Selection, 2011)
Imagine strolling along the windy shores of Jeju Island, off the southwest coast of Korea. Suddenly, you hear whistling echoing from the sea. Turning to the water, you spot weathered faces bobbing to the surface, and you realize that the sound is the exhaled breath of sea women, known as haenyeo. With a sigh of gratitude, the aging divers have returned to the surface to replenish their aching lungs. Jeju Island's haenyeo are a dying breed perhaps the last of their generation. As their maternal ancestors did for centuries, they have scoured the island's sea floor, harvesting seaweed, octopuses,